Niat Berwirausaha: Peran Pengetahuan Kewirausahaan dan Grit - Salsabila, Pahira; Siswandari, Siswandari; Sabandi, Muhammad (Jurnal Ragam Pengabdian, 2026)
This study aims to examine how grit functions as a mediator in the relationship between entrepreneurial intention and entrepreneurial knowledge. This research employed a survey method with a quantitative approach. The sampling method used was simple random sampling, resulting in 100 respondents from various undergraduate study programs at Sebelas Maret University. Data were collected using a closed-ended questionnaire in the form of a Likert scale with five response options. The statistical analysis tool used to test the mediation effect in this study was IBM SPSS Statistics 27 software. The findings indicate that students’ entrepreneurial intentions can be influenced by entrepreneurial knowledge, with grit acting as a mediating variable. To enhance and develop knowledge that encourages entrepreneurial intentions, higher education institutions or universities should improve the quality of teaching materials and teaching methods, while also focusing on enhancing both academic and psychological skills. In addition, universities should create a supportive environment for young entrepreneurs by emphasizing entrepreneurial values to foster the development of entrepreneurial knowledge, entrepreneurial intentions, and grit among students.